PLACENTA ACCRETA – RISK FACTORS, SURGICAL AND CLINICAL OUTCOME - Mariana Tsankova; Sergei Slavov; Ivan Kostov (Journal of IMAB)
Placenta accreta is a spectrum of antenatal diagnostic markers, surgical complications and life-threatening diagnoses. Objective: To evaluate the risk factors, the surgical complications and the clinical peripartal outcomes in the placenta accreta spectrum. Materials and methods: The study represents an 11-year prospective follow-up of 58 cases of placenta accreta, sonografically diagnosed, clinically managed and pathohystologically confirmed. The rate of placenta accreta was 34,5%, placenta percreta - 56,9% and partial placenta accreta 8.6%. In The main risk factors were a previous caesarean section and placenta previa. Additional risk factors were advanced maternal age, multiparity, IVF procedures, previous uterine curettage, anterior placenta. The control group consisted of 135 cases with normal placenta. Results: We found an increaseed rate of caesarean births and a corresponding increase in placenta previa rate. The peripartal hysterectomy rate was 91%. Surgical complications were mostly uterovesical lesions and excessive haemorrhage. Blood loos in the groups with an emergency hysterectomy and ralaparotomy was in the range of 3510 ml – 6500 ml, compared to 3420 ml in planed delivery with caesarean hysterectomy due to placenta accreta. More resuscitation measures and longer hospital stay was observed in cases with a placenta accreta spectrum. The neonatal clinical outcome was good according to fetal weight and Apgar score at delivery. Conclusion: Our results revealed good clinical confirmation in 90% of cases by expert ultrasonographers, followed by clinical and histopathological confirmation in all cases. This diagnosis and its surgical treatment will continue to be a professional challenge.